MICROWAVE-ASSISTED SYNTHESIS OF REDUCED TITANIA USING NABH4 AS REDUCING AGENT FOR PHOTOCATALYTIC DEGRADATION OF SYNTHETIC DYES AT VISIBLE LIGHT - Reinaldo, Ricky
Synthetic dyes are included in Persistent Organic Pollutants (POPs) which cannot be removed by ordinary conventional methods, therefore it is necessary to remove them by photocatalyst methods. Current commercial photocatalysts are TiO2 or titania, but titania is considered less effective as a photocatalyst because of its large band gap value so that titania can only absorb energy in the UV spectrum. To overcome this problem, it is necessary to modify titania by reducing the energy that can be absorbed not only from UV light, but also from the visible light region. There are 3 research parameters in this final project, namely heating method (microwave and tube furnace), distillation time (2, 5 and 8 hours) and NaBH4 concentration (0 wt%, 27.5 wt%, 40 wt% and 50 wt%) used. Reduction on titania was carried out in accordance with the variation of research parameters that have been set. After obtaining reduced titania specimens, characterization was carried out to ensure that the synthesized specimens were reduced titania through XRD, SEM, DRS, UV-VIS testing and comparing the photodegradation performance of each specimen in visible light. Based on the experiments conducted, the best heating method to do is microwave heating method, the most optimal distillation time is 5 hours and the concentration of NaBH4 that gives the most optimal results is 50wt%. From this study, it was concluded that the microwave-assisted synthesis of reduced titania using NaBH4 as a reducing agent was successful because it showed an increase in photocatalytic activity in visible light in degrading synthetic dyes.